Acute and subacute toxicity studies of chitosan reduced gold nanoparticles: a novel carrier for therapeutic agents - Pokharkar, Varsha; Dhar, Sheetal; Bhumkar, Devika; Mali, Vishal; Bodhankar, Subhash L.; Bhagavatula L. V. Prasad (Journal of Biomedical Nanotechnology, 2009)
The objective of the present study was to evaluate the oral toxicity of chitosan reduced gold nanoparticles so as to demonstrate its applicability for drug delivery application. Acute oral toxicity studies in female rats documented no deaths or treatment related complications. The LD(50) value of gold nanoparticles was found to be greater than 2000 mg/kg. In case of sub-acute oral toxicity studies, gold nanoparticles were administered orally to male and female rats for a period of 28-days. At the end of study blood samples were collected for haematology and biochemical analysis. For histopathological analysis, organs of animals were weighed and processed for examination. All animals survived the duration of the study, with no significant changes in clinical signs, body weight, food consumption, hematological parameters, organ weights and histopathological findings. These studies establish that chitosan reduced gold nanoparticles produced no treatment related toxicity in rats following oral administration, thus can be exploited for potential therapeutic applications.
Keywords: Acute Toxicity; Chitosan; gold nanoparticles; Sub-Acute Toxicity; Wistar Rats

Biocompatible gellan gum-reduced gold nanoparticles: cellular uptake and subacute oral toxicity studies - Dhar, Sheetal; Mali, Vishal; Bodhankar, Subhash L.; Shiras, Anjali; Bhagavatula L. V. Prasad; Pokharkar, Varsha (Journal of Applied Toxicology, 2011)
Currently gold nanoparticles are being explored for drug delivery and other biomedical applications; therefore it is necessary to study the fate of such nanoparticles inside the body. The objective of the present study was to investigate the cellular uptake and toxicity of the gold nanoparticles synthesized using a microbial polysaccharide, gellan gum, as a capping and reducing agent. The cellular uptake of gold nanoparticles was studied on mouse embryonic fibroblast cells, NIH3T3 and human glioma cell line, LN-229. The cellular uptake study indicated that the gellan gum-reduced gold nanoparticles were located in cancer cells (LN-229) while no uptake was observed in normal mouse embryonic fibroblast cells (NIH3T3). The toxicity of the gold nanoparticles was evaluated by carrying out subacute 28 day oral toxicity studies in rats. Subacute administration of gum-reduced gold nanoparticles to the rats did not show any hematological or biochemical abnormalities. The weight and normal architecture of various organs did not change compared with control. The current findings, while establishing the specific uptake of nanoparticles into cancerous cells, also demonstrates that the gellan gum-reduced gold nanoparticles are devoid of toxicity in animals following oral administration. Copyright (c) 2010 John Wiley & Sons, Ltd.
Keywords: cell lines; cellular uptake; Gellan gum; gold nanoparticles; subacute toxicity

Proteomic analysis of protease resistant proteins in the diabetic rat kidney - Bansode, Sneha B.; Chougale, Ashok D.; Joshi, Rakesh S.; Giri, Ashok P.; Bodhankar, Subhash L.; Harsulkar, Abhay M.; Kulkarni, Mahesh J. (Molecular & Cellular Proteomics, 2013)
Glycation induced protein aggregation has been implicated in the development of diabetic complications and neurodegenerative diseases. These aggregates are known to be resistant to proteolytic digestion. Here we report the identification of protease resistant proteins from the streptozotocin induced diabetic rat kidney, which included enzymes in glucose metabolism and stress response proteins. These protease resistant proteins were characterized to be advanced glycation end products modified and ubiquitinated by immunological and mass spectrometry analysis. Further, diabetic rat kidney exhibited significantly impaired proteasomal activity. The functional analysis of identified physiologically important enzymes showed that their activity was reduced in diabetic condition. Loss of functional activity of these proteins was compensated by enhanced gene expression. Aggregation prone regions were predicted by in silico analysis and compared with advanced glycation end products modification sites. These findings suggested that the accumulation of protein aggregates is an inevitable consequence of impaired proteasomal activity and protease resistance due to advanced glycation end products modification. Molecular & Cellular Proteomics 12: 10.1074/mcp.M112.020651, 228-236, 2013.

Isolation, characterization and antihyperlipidemic activity of secoisolariciresinol diglucoside in poloxamer-407-induced experimental hyperlipidemia - Zanwar, Anand A.; Hegde, Mahabaleshwar V.; Rojatkar, Supada R.; Sonawane, Kiran B.; Rajamohanan, P. R.; Bodhankar, Subhash L. (Pharmaceutical Biology, 2014)
Context: Linum usitatissimum L. (Linaceae), commonly known as flaxseed, is a good source of dietary fiber and lignans. Earlier we reported cardioprotective, antihyperlipidemic, and in vitro antioxidant activity of flax lignan concentrate (FLC) obtained from flaxseed. Objectives: To isolate secoisolariciresinol diglucoside (SDG) from FLC and to evaluate the antihyperlipidemic activity of SDG in poloxamer-407 (P-407)-induced hyperlipidaemic mice. Material and methods: FLC was subjected to column chromatography and further subjected to preparative HPTLC to isolate SDG. The chemical structure of the isolated compound was elucidated by UV, IR, H-1 NMR, C-13 NMR, DEPT, COSY, HSQC, HMBC, ROESY, MS, and specific optical rotation was recorded. Further, we have investigated the antihyperlipidaemic effect of SDG (20 mg/kg) in P-407-induced hyperlipidaemic rats. Hyperlipidaemia was induced by intraperitoneal administration of P-407 (30% w/v). Serum lipid parameters such as total cholesterol (TC), triglycerides (TG), and high-density lipoprotein cholesterol (HDL-C) levels were measured. Results and discussion: The structure and stereochemistry of the isolated compound were confirmed on the basis of 1D and 2D spectral data and characterized as SDG. Finally, isolated pure SDG was screened using a P-407-induced mice model for its antihyperlipidemic action using serum lipid parameters. The isolated SDG (20 mg/kg) significantly reduced serum cholesterol, triglyceride (p<0.001), very low-density lipoprotein (p<0.05), and non-significantly increased HDL-C. Conclusion: Finally, it was concluded unequivocally that SDG showed antihyperlipidaemic effects in P-407-induced hyperlipidaemic mice. Isolated pure SDG confirms that SDG is beneficial in the prevention of experimental hyperlipidemia in laboratory animals.
Keywords: column chromatography; flaxseed; Linum usitatissimum

Isolates of alpinia officinarum hance as COX-2 inhibitors: evidence from anti-inflammatory, antioxidant and molecular docking studies - Honmore, Varsha S.; Kandhare, Amit D.; Kadam, Parag P.; Khedkar, Vijay M.; Sarkar, Dhiman; Bodhankar, Subhash L.; Zanwar, Anand A.; Rojatkar, Supada R.; Natu, Arun D. (International Immunopharmacology, 2016)
Background: Inflammation triggered by oxidative stress can cause various ailments, such as cancer, rheumatoid arthritis, asthma, diabetes etc. In the last few years, there has been a renewed interest in studying the antioxidant and anti-inflammatory action of plant constituents such as flavonoids and diarylheptanoids. Aim: To evaluate the antioxidant, anti-inflammatory activity and the total phenolic content of isolated compounds from Alpinia officinarum rhizomes. Furthermore, molecular docking was performed to study the binding mode of these compounds into the active site of cyclooxygenase-2 (COX -2). Methods: A. officinarum rhizomes were extracted by maceration, using methanol. This extract was further fractionated by partitioning with hexane, chloroform and ethyl acetate and these fractions on further purification resulted in isolation of five pure compounds. Characterization was carried out by using H-1 NMR, C-13 NMR and MS. They were further evaluated for antioxidant and anti-inflammatory activity using carrageenan-induced paw edema model in rats. Molecular docking study was performed using Glide module integrated in Schrodinger molecular modeling software. Results: The compounds were identified as 1,7-diphenylhept-4-en-3-one (1), 5-hydroxy-1,7-diphenyl-3-heptanone (2), 3,5,7-trihydroxyflavone (Galangin, 3), 3,5,7-trihydroxy-4'-methoxyflavone (Kaempferide, 4) and 5-hydroxy-7-(4 `'-hydroxy-3 `'-methoxyphenyl)-1-phenyl-3-heptanone (5). The compound-3 and compound-5 (10 mg/kg) showed significant (p < 0.001) antioxidant and anti-inflammatory potential. Moreover, total phenolic content was detected as 72.96 mg and 51.18 mg gallic acid equivalent respectively. All the five isolates were found to be good binders with COX-2 (average docking score -9.03). Conclusions: Galangin and 5-hydroxy-7-(4 `'-hydroxy-3 `'-methoxyphenyl)-1-phenyl-3-heptanone exhibited anti-inflammatory and in-vitro antioxidant activity which may be due to presence of phenolic content in it. The molecular docking study revealed that these compounds have affinity towards COX-2 active site which can further be explored as selective COX-2 inhibitors. The results obtained in this work justify the use of A. officinarum in the treatment of inflammatory disorders like rheumatoid arthritis and inflammatory bowel diseases. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: 5-Hydroxy-7-(4 `'-hydroxy-3 `'-methoxyphenyl)-1-phenyl-3-heptanone; Alpinia officinarum; Anti-inflammatory; Antioxidant; COX-2 inhibitors; Galangin